Productivity Analysis Using the Critical Chain Project Method Management (CCPM) on Repair Projects Geomarin-III ship 649 DWT. - Ari Wibawa Budi Santosa; Ocid Mursid; Muhamad Angger Kalingga; Syaiful Tambah Putra Ahmad; Andi Trimulyono (International Journal of Marine Engineering Innovation and Research, 2023)
Ship repair project planning still often encountered problems that delay ship repair projects to achieve complete ship repair projects. Delays are due to frequent mismatches between ship repair scheduling and conditions that occur at the shipyard. The most commonly used method is the Critical Path Method (CPM). But in reality, the CPM method is considered less effective because there is still safety time for each job. Technological developments found the latest method, namely Critical Chain Project Management (CCPM). This method removes the safety time contained in the CPM method and replaces it with buffer time which is placed at the end of work activities. This study aims to analyze the duration of the critical path, determine labor costs, and the amount of buffer duration on the repair of the Geomarin-III 649 DWT ship. Based on the calculation results obtained on the repair of the Geomarin-III 649 DWT ship with the Critical Chain Project Management (CCPM) method is 10 days, 10 days faster than the normal duration. The labor cost obtained using the CCPM method is IDR. 54,017,500, saving 35% of the normal cost is IDR. 82,680,000, but if the buffer time is used thoroughly, the total estimated labor cost for the CCPM method will increase due to the addition of labor and the duration of the buffer time obtained by the CCPM method as a substitute for safety time, which is 9 days project buffer and 3 days feeding buffers. Based on this research, it was found that the CCPM method is considered effective and can accelerate the duration of the project and minimize labor costs.